Dory Dory black sheep - Hanlon, Abby (Hanlon, Abby. Dory Fantasmagory., 2016)
"When Dory's best friend learns to read before she does, Dory retreats into her wild imagination and finds herself in the middle of one of the babyish books she is struggling to read where she encounters imaginary friends and enemies"--